Assessment of blood cultures and antibiotic susceptibility testing for bacterial sepsis diagnosis and utilization of results by clinicians in Benin: A qualitative study - Legba, Brice Boris; Dougnon, Victorien; Koudokpon, Hornel; Mero, Sointu; Elovainio, Riku; Parry, Matti; Bankole, Honoré; Haukka, Kaisa (Frontiers in Public Health, 2023)
Objectives: We assessed the current status of blood culture and antibiotic susceptibility testing (AST) practices in clinical laboratories in Benin, and how the laboratory results are used by physicians to prescribe antibiotics. Methods: The qualitative study covered twenty-five clinical laboratories with a bacteriology unit and associated hospitals and pharmacies. Altogether 159 laboratory staff, physicians and pharmacists were interviewed about their perceptions of the state of laboratory diagnostics related to sepsis and the use of antibiotics. Face-to-face interviews based on structured questionnaires were supported by direct observations when visiting five laboratories in across the country. Results: Only 6 laboratories (24%) conducted blood cultures, half of them with a maximum of 10 samples per month. The most common gram-negative bacteria isolated from blood cultures were: Escherichia coli, Salmonella spp. and Salmonella enterica serovar Typhi while the most common gram-positives were Enterococcus spp. and Staphylococcus aureus. None of the laboratories listed Klebsiella pneumoniae among the three most common bacteria isolated from blood cultures, although other evidence indicates that it is the most common cause of sepsis in Benin. Due to limited testing capacity, physicians most commonly use empirical antibiotic therapy. Conclusions: More resources are needed to develop laboratory testing capacity, technical skills in bacterial identification, AST, quality assurance, and communication of results must be strengthened.